1995
DOI: 10.1007/bf00192493
|View full text |Cite
|
Sign up to set email alerts
|

Membrane and firing properties of avian medial vestibular nucleus neurons in vitro

Abstract: The intrinsic membrane and firing properties of medial vestibular nucleus (MVN) neurons were investigated in slices of the chick brainstem using intracellular recording and current injection. Avian MVN neurons fired spontaneous action potentials with very regular interspike intervals. The rapid repolarization of all action potentials was followed by an afterhyperpolarization. Intracellular injection of steps of hyperpolarizing current revealed both an inward rectification of the membrane potential during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
(60 reference statements)
0
28
0
Order By: Relevance
“…Thus the question arises whether the results of our in vivo studies can be related to previous in vitro characterizations of mouse VN neurons. In vitro studies have shown that VN neurons can be separated into two groups (type A and B) based on the shape of their action potentials and the subsequent after hyperpolarization (du Lac and Lisberger 1995;Johnston et al 1994;Serafin et al 1991). Although most of type A are GABAergic neurons, type B MVN neurons are either GABAergic, glutamatergic or glycinergic (Bagnall et al 2007;Takazawa et al 2004).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 99%
“…Thus the question arises whether the results of our in vivo studies can be related to previous in vitro characterizations of mouse VN neurons. In vitro studies have shown that VN neurons can be separated into two groups (type A and B) based on the shape of their action potentials and the subsequent after hyperpolarization (du Lac and Lisberger 1995;Johnston et al 1994;Serafin et al 1991). Although most of type A are GABAergic neurons, type B MVN neurons are either GABAergic, glutamatergic or glycinergic (Bagnall et al 2007;Takazawa et al 2004).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 99%
“…The soma transforms the synaptic current u i into a firing rate v i , according to some rate-current relationship. According to measurements in MVN slices (20)(21)(22), this relationship is roughly linear above threshold:…”
Section: Linear Network Modelsmentioning
confidence: 99%
“…For every position of the eyes, the pattern of activity is different, and can persist much longer than the intrinsic persistence time of a single neuron's activity (20)(21)(22). Therefore, the long persistence of network activity appears to be a collective effect that depends on the interactions between the neurons of the memory network.…”
mentioning
confidence: 99%
“…Many neurons fire regular, spontaneous, sodium-dependent action potentials, even in the absence of synaptic input (Llinás and Sugimori, 1980;Williams et al, 1984;Jahnsen, 1986a;Grace and Onn, 1989;Yung et al, 1991;du Lac and Lisberger, 1995;Mouginot and Gähwiler, 1995;Uteshev et al, 1995;Bayliss et al, 1997). Spontaneous firing can be generated in several ways.…”
Section: Abstract: Deep Cerebellar Nuclei; Pacemaking; Action Potentmentioning
confidence: 99%